METHODS FOR PREDICTING THE LITHOLOGICAL AND FACIES CHARACTERIZATION OF DEEPLY SUBMERGED PROSPECTIVE OIL AND GAS DEPOSITS - Aliyeva, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
These studies aimed at clarifying the formation characteristics of the Lower Miocene - the Paleogene of the region under consideration, in connection with the prospects of oil and gas potential. For this purpose, a predictive assessment was made of the formation characteristics of the deeply submerged formations of the Lower Miocene - the Paleogene of the western side zone of the South Caspian megavalley (mainly the Nizhnekurinsky oil and gas region (NGO)) in connection with the prospects of oil and gas potential. In addition, we used the results of studies of emissions of mud volcanoes located in the considered zone (the Nizhnekurinsky Depression and adjacent zones of the South Caspian shelf). As a result of the study of drilling data in the adjacent areas of the Kobystan-Shemakha, Pre-Talysh and Yevlakh-Agdzhabedy troughs, data were obtained on the formation characteristics of the Lower Miocene-Paleogene deposits composing this zone.To the most promising areas for the preliminary stage of exploration for oil and gas (at the Lower-Miocene-Paleogene complex) of the western side of the Southeast, on the totality of lithologic-facial and tectonic criteria of oil and gas content, it is possible to attribute Duvanny, Kyanizadag, Sangachal- Khara Zyrya, Koturdag, Dashgil, Hamamdag, Agzibir, Kursangya areas.